SOCIAL AND ECONOMIC LIFE OF SAMARKAND DURING THE REIGN OF THE EMIRATE OF BUKHARA - Shertaylaqova, G (Мир исследований, 2021)
This article gives an idea of the social and economic life of Samarkand during the reign of the emirate of Bukhara.